FORMATION OF STRATEGIES FOR THE DEVELOPMENT OF ENERGY COMPANIES - E. Kamchatova; M. Sukhova (Вестник университета)
In a dynamically changing economic environment and external circumstances energy companies have forced to pay more attention to the searching for management solutions, aimed at their effective functioning. This diffcult task can be solving by forming a strategy for their development. For this purpose, the article presents the results of the studying of the main behavioural strategies of energy companies, the analysis of the business strategies of the dominant energy companies operating in the electricity and power market